2018
DOI: 10.3390/molecules23092140
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the In Vivo and In Vitro Metabolites of Linarin in Rat Biosamples and Intestinal Flora Using Ultra-High Performance Liquid Chromatography Coupled with Quadrupole Time-of-Flight Tandem Mass Spectrometry

Abstract: Linarin, a flavone glycoside, is considered to be a promising natural product due to its diverse pharmacological activities, including analgesic, antipyretic, anti-inflammatory and hepatoprotective activities. In this research, the metabolites of linarin in rat intestinal flora and biosamples were characterized using ultra-high-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF-MS/MS). Three ring cleavage metabolites (4-hydroxybenzoic acid, 4-hydroxy benzaldehyde and phlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The corresponding ESI-MS 2 spectrum featured product ions with m/z 281.0782, 255.0997, and 253.0843 produced by loss of H 2 O, CO 2 , and H 2 O + CO, respectively, while the product ion with m/z 205.0483 was formed through C2–C1′ bond cleavage. Additionally, secondary ions with m/z 179.0333 and 119.0493 were produced by retro-Diels−Alder (RDA) cleavage of ring C, and this reaction was concluded to be a representative flavonoid fragmentation pathway allowing rapid metabolite identification [21,27,28]. The MS/MS spectra and fragmentation pathways of farrerol are presented in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding ESI-MS 2 spectrum featured product ions with m/z 281.0782, 255.0997, and 253.0843 produced by loss of H 2 O, CO 2 , and H 2 O + CO, respectively, while the product ion with m/z 205.0483 was formed through C2–C1′ bond cleavage. Additionally, secondary ions with m/z 179.0333 and 119.0493 were produced by retro-Diels−Alder (RDA) cleavage of ring C, and this reaction was concluded to be a representative flavonoid fragmentation pathway allowing rapid metabolite identification [21,27,28]. The MS/MS spectra and fragmentation pathways of farrerol are presented in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The two major product ions with m/z 285.0760 and 269.0800 were ascribed to loss of CO and CO 2 , respectively [30]. RDA cleavage afforded ions with m/z 193.0121 (Δ = 14 Da) and 119.0495 [21]. Based on the above, M15 and M16 were identified as 8-ketofarrerol and 6-ketofarrerol, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed from the concentration–time curve that tenacissoside B, I, H and G had double peaks, which might be associated with enterohepatic and enteric circulation (Feng et al, 2018; Wang, Bao, Wang, Li, & Meng, 2019). Those pharmacokinetic profiles suggested that the maximal concentrations of neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, caffeic acid, tenacissoside B, I and G were apparently achieved after 0.25 and 0.5 h for tenacissoside H, revealing that these analytes were rapidly absorbed in rat blood.…”
Section: Resultsmentioning
confidence: 99%
“…However, one of our previous studies revealed that linarin shows low bioavailability (0.47%) after oral administration, which suggests that linarin could be extensively metabolized after oral administration, and the metabolites of linarin could still show various pharmacological activities [11]. Acacetin, apigenin, and p -hydroxy benzaldehyde (Figure 1) have been identified as the metabolites of linarin [12]. We found that these three metabolites showed a protective effect against severe d -GalN-induced hepatic failure in rats (data not shown).…”
Section: Introductionmentioning
confidence: 99%